2013
DOI: 10.1039/c3cc47130f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proportion of radiative excitons in non-doped electro-fluorescence generated from an imidazole derivative with an orthogonal donor–acceptor structure

Abstract: A greatly enhanced proportion of radiative excitons in non-doped blue electroluminescence with a maximum exciton utilizing efficiency (EUE) of 85% is harvested in the orthogonal cyano substituted, charge transfer (CT) emitter TPMCN, in comparison to the localized emission (LE)-like emitter TPM with a low EUE of 16%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 207 publications
(93 citation statements)
references
References 17 publications
2
91
0
Order By: Relevance
“…However, the host‐guest system subsequently requires simultaneously depositing two different materials by controlling the evaporation speed and ratio of each material. The introduction of the non‐doped device configuration can simplify the evaporation process and lower the cost in the industrial production, and hence is much more favorable than the co‐deposition procedure . The non‐radiative process, in non‐doped devices, can be suppressed by either largely twisted molecular conformation or through interference with the molecular stacking; one of the major causes of non‐radiative quenching.…”
Section: Tadf Molecular Design Towards Efficient Oleds With Superior mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the host‐guest system subsequently requires simultaneously depositing two different materials by controlling the evaporation speed and ratio of each material. The introduction of the non‐doped device configuration can simplify the evaporation process and lower the cost in the industrial production, and hence is much more favorable than the co‐deposition procedure . The non‐radiative process, in non‐doped devices, can be suppressed by either largely twisted molecular conformation or through interference with the molecular stacking; one of the major causes of non‐radiative quenching.…”
Section: Tadf Molecular Design Towards Efficient Oleds With Superior mentioning
confidence: 99%
“…The introduction of the non-doped device configurationc an simplify the evaporation process and lower the cost in the industrial production,a nd hence is much more favorable than the codeposition procedure. [62] The non-radiative process, in nondopedd evices,c an be suppressedb ye ither largely twisted molecular conformation or throughi nterference with the molecular stacking;o ne of the major causes of non-radiative quenching. Up to now,t he mostc ommonly adopted EWGs that can potentially induce non-doped TADF are sulfone, [14b] triazine, [14a] benzimidazole, [20f] andc arbonyl-containing groups, [63] etc (Figure 13).…”
Section: Design Of Tadf Molecules With Non-doped Capabilities In Tadfmentioning
confidence: 99%
“…Recently, we achieved a series of donor-acceptor molecules with HLCT state after the careful manipulation of the distance, torsion angle and strength between the donor and acceptor moieties [7,8,33,34,47,54,55]. The quantified natural transition orbital (NTO) analysis indicated that the holes and particles of such molecules always exhibited obvious orbital separation and certain orbital overlap simultaneously.…”
Section: The Design Principle For the S 1 State Of Hot Exciton Materialsmentioning
confidence: 99%
“…Where, the excited state µ e was smaller and near to 10 D, and the LE state was dominant component to S 1 . If µ e was larger than the typical CT molecule DMABN of 23 D, the CT state was dominant component. Between the both, the mixed state was considered as a hybridized composition containing LE and CT component.…”
Section: Resultsmentioning
confidence: 99%